Modeling of crude oil biodegradation using two phase partitioning bioreactor - Ahmadun, Fakhru'l-Razi; Peyda, Mazyar; Wan Ab Karim Ghani, Wan Azlina; Zainal Abidin, Zurina; Zakaria, Mohamad Pauzi; Moeini, Hassan (Wiley-Blackwell Publishing, 2014)
In this work, crude oil biodegradation has been optimized in a solid-liquid two phase partitioning bioreactor (TPPB) by applying a response surface methodology based d-optimal design. Three key factors including phase ratio, substrate concentration in solid organic phase, and sodium chloride concentration in aqueous phase were taken as independent variables, while the efficiency of the biodegradation of absorbed crude oil on polymer beads was considered to be the dependent variable. Commercial thermoplastic polyurethane (Desmopan®) was used as the solid phase in the TPPB. The designed experiments were carried out batch wise using a mixed acclimatized bacterial consortium. Optimum combinations of key factors with a statistically significant cubic model were used to maximize biodegradation in the TPPB. The validity of the model was successfully verified by the good agreement between the model-predicted and experimental results. When applying the optimum parameters, gas chromatography-mass spectrometry showed a significant reduction in n-alkanes and low molecular weight polycyclic aromatic hydrocarbons. This consequently highlights the practical applicability of TPPB in crude oil biodegradation.